Maternal History of Hypertension and Blood Pressure Response to Potassium Intake: The GenSalt Study - Kelly, Tanika N. (Oxford University Press, 2012)
The relation between parental history of hypertension and blood pressure response to potassium intake is unknown. A 7-day high-sodium followed by a 7-day high-sodium plus potassium dietary-feeding study was conducted from 2003 to 2005 among 1,871 Chinese participants. Those with a maternal history of hypertension had larger systolic blood pressure responses to potassium compared with those without: −4.31 (95% confidence interval (CI): −4.99, −3.62) mm Hg versus −3.35 (95% CI: −4.00, −2.70) mm Hg, respectively (P(difference) = 0.002). A consistent trend was observed for diastolic blood pressure responses: −1.80 (95% CI: −2.41, −1.20) mm Hg versus −1.35 (95% CI: −1.95, −0.74) mm Hg, respectively (P = 0.07). Stronger associations between early onset maternal hypertension and blood pressure responses were noted, with systolic blood pressure decreases of −4.80 (95% CI: −5.65, −3.95) mm Hg versus −3.55 (95% CI: −4.17, −2.93) mm Hg and diastolic blood pressure decreases of −2.25 (95% CI: −3.01, −1.50) mm Hg versus −1.42 (95% CI: −1.99, −0.85) mm Hg among those with early onset maternal hypertension versus those without, respectively (P = 0.001 and 0.009, respectively). Odds ratios for high potassium sensitivity were 1.36 (95% CI: 0.96, 1.92) and 1.60 (95% CI: 1.08, 2.36) for those with maternal hypertension and early onset maternal hypertension, respectively (P = 0.08 and 0.02, respectively). Potassium supplementation could help to reduce blood pressure among those with a maternal history of hypertension.